Determining the Phase Separation Characteristics of Plant Proteins. Issue 9 (9th September 2021) - Liu, Qing; Liu, Yang; Li, Qi; Qian, Weiqiang; Zhang, Xiaoming
Abstract: Eukaryotic cells contain numerous membrane‐bound and membraneless organelles that provide spatiotemporal control for diverse biological processes. The liquid–liquid phase separation of proteins has been proposed as the driving force behind the formation of membraneless organelles. Here, we describe a method to determine the phase separation activities of proteins in plants. This basic method includes protocols for an in vivo fluorescence recovery after photobleaching assay in Nicotiana benthamiana using transient expression, an in vitro liquid droplet reconstitution assay using purified recombinant proteins, and an in vivo fluorescence recovery after photobleaching assay in Arabidopsis thaliana using stable transgenic plants. With these assays, the phase separation characteristics of a protein can be determined. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Detection of protein phase separation activities in N. benthamiana Support Protocol : Fluorescence recovery after photobleaching assay Basic Protocol 2 : Detection of protein phase separation in vitro Basic Protocol 3 : Detection of protein phase separation in stable transgenic Arabidopsis thaliana plants